Dairy industry sewage sludge as a fertilizer for an acid soil: a laboratory experiment with Lolium multiflorum L. - Conde Suarez, P.=700 1 Seoane, S.; Lopez Mosquera, E.; Solla-Gullon, F.; Merino, A.
(Es, En)
ilus., 28 ref.
Keywords: LOLIUM MULTIFLORUM; APLICACION DE ABONOS; LODOS RESIDUALES; NUTRIENTES; ESPAÑA; BALANCE DE NUTRIENTES; RAIGRAS